167k views
5 votes
Solve the equation.

5x + 6 = 2(2x – 3)

what dose x =

User Zerodin
by
5.5k points

2 Answers

3 votes

Answer:

5x + 6 = 2(2x-3)

5x + 6 = 4x -5

x + 6 = -5

......x = -11......

User Jerven Clark
by
5.6k points
4 votes

Answer:

x=−12

Explanation:

Let's solve your equation step-by-step.

5x+6=2(2x−3)

Step 1: Simplify both sides of the equation.

5x+6=2(2x−3)

5x+6=(2)(2x)+(2)(−3)(Distribute)

5x+6=4x+−6

5x+6=4x−6

Step 2: Subtract 4x from both sides.

5x+6−4x=4x−6−4x

x+6=−6

Step 3: Subtract 6 from both sides.

x+6−6=−6−6

User Amit Rana
by
6.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.